Study on the impact of Kinesiophobia after Total Knee Arthroplasty on the rehabilitation of patients during hospitalization: A pilot study - Yichao Yao; Qi Zhang; Shaoning Cui; Xumeng Guo (PLoS ONE, 2025)
The purpose of this study is to investigate the influence of kinesiophobia following Total Knee Arthroplasty (TKA) on the rehabilitation outcomes of patients during hospitalization, includes examining the trends in resting pain levels at various time points post-surgery, the trends in active flexion of the knee at various time points post-surgery, and the effects of kinesiophobia on the timing of first postoperative ambulation, the duration of postoperative hospital stay, and the results of the two-minute walk test on the day of discharge. Postoperative kinesiophobia in patients was identified using the Tampa Scale for Kinesiophobia (TSK), with 33 patients scoring >37 points and 35 patients scoring ≤37 points. Resting Pain levels were assessed using the Numerical Rating Scale (NRS) at various time points, including upon return to the ward (T1), the first (T2), second (T3), third (T4), fifth(T5) postoperative days, and the day of discharge (T6). Furthermore, active flexion of the knee joint was measured at different time points for both groups, including the first (T1*), third (T2*), and fifth (T3*) postoperative days, and the day of discharge (T4*). The first time out of bed activities of the two groups of patients were compared, along with the results of the 2-Minute Walk Test (2-MWT) on the day of discharge. The pain scores of patients in the kinesiophobia group at different time points after surgery were worse than those in the non-kinesiophobia group (P<0.05). There were significant time effects (F = 131.297;P<0.01), inter-group effects (F = 15.016; P<0.01), and interaction effects (F = 5.116; P<0.05). The active knee flexion of patients in the kinesiophobia group at different time points after surgery were worse than those in the non-kinesiophobia group (P<0.05).There were significant time effects (F = 628.258;P<0.01), inter-group effects (F = 16.546; P<0.01), and interaction effects (F = 66.025; P<0.01). Patients in the kinesiophobia group delayed getting out of bed for the first time (35.39±9.82vs28.77±9.81hours; P<0.01), had shorter activity time (4.12±1.36vs5.80±1.96minutes; P<0.01) and distance (19.12±3.36vs30.17±5.64meters;P<0.01), and experienced higher pain scores during activity (6.30±1.10vs5.48±0.95scoresP<0.05). Additionally, patients in the kinesiophobia group walked shorter distances in the 2-MWT test on the day of discharge compared to the non-kinesiophobia group (37.60±5.76vs50.68±5.37meters;P<0.05), and had longer hospitalization time (8.11±1.31vs50.68±5.37days; P<0.05). In short, compared to patients without kinesiophobia, the presence of kinesiophobia after TKA surgery significantly impacts the efficacy of early rehabilitation exercises during hospitalization. This impact is observed in pain perception, knee joint mobility, the 2-minute walk test, etc. Early identification of patients with kinesiophobia after TKA and timely intervention are necessary and beneficial.